THE AESTHETICISATION OF TASTE, A CONSEQUENCE OF THE “AESTHETICISATION” OF BEAUTY - Talon-Hugon, Carole (The Nordic Journal of Aesthetics, 2018)
At the beginning of modern times, taste was seen as a sort of sense of sociability, indistinctly moral and aesthetic. Why, during the eighteenth century did it become exclusively the sense of beauty? To understand this change, this article maintains that we must consider the great revolution, which affected the idea of beauty between the seventeenth and the eighteenth centuries, that is to say the end of the metaphysical conception of beauty. We must analyse the phenomenon of beauty aestheticisation produced by the modern subjectivist, psychological and empirical perspective. The aestheticisation of taste is one of the consequences of the underground ontological revolution, which led to a transformation of the transcendental essences in human values. When beauty is nothing more than beauty, and does not exist without a sensitive experience, one needs a sensitive faculty which enables one to grasp beauty, or more precisely, which gives birth to beauty, seeing beauty as no longer having a proper ontological consistency.